Cued speech: full access to spoken language for the hearing impaired - Guita Movallali (Auditory and Vestibular Research, 2017)
Background and Aim: A system that could make speech visible to deaf people has been dreamt of for long time. Several systems have been developed during recent decades; with the most popular being cued speech invented 50 years ago by Cornett (1967). The aim of this article is to review researches about cued speech and its efficacy on different language skills of hearing impaired children. Methods: In this article we reviewed researches on cued peech and its impacts on speech and literacy of hearing impaired children. We searched Medline, Proquest and Scopus search engines with the “cued speech” keyword and read all textbooks and thesis published between 1972 and 2011. Cued speech is an oral system which makes the sounds visible and accessible. It makes speech perception much simpler and improves lip-reading skills and ability of using residual hearing in hearing impaired children. Conclusion: Cued speech enhances children’s communication and speech perception and discrimination from early ages. It improves speech and ability to benefit from cochlear implantation. The original impetus behind cued speech was to improve literacy levels of hearing impaired children and it has been found to be uniquely successful.